PENGARUH SOCIAL MEDIA MARKETING DAN CELEBRITY ENDORSMENT DALAM MENINGKATKAN PURCHASE INTENTION YANG DIMEDIASI OLEH COSTUMER TRUST PADA ONLINE SHOP SHOPEE DI KOTA BANDA ACEH - Dinah Mahirah; Syarifah Evi Zuhra (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
The purpose of this study was to analyze the effect of social media marketing, celebrity endorsements, and customer trust on purchase intentions at Shopee's online store. The type of research used is quantitative research. The target population of this study is domiciled in Banda Aceh City and is a consumer of Shoppe and has shopped for products from Shopee at least twice. The sample taken in this study amounted to 150. The data analysis technique used in this study was The Structural Equation Modeling (SEM) from the AMOS statistical software package for hypothesis testing.The results show that social media marketing has a role that can have a positive and significant influence on purchase intentions at shopee online stores. With celebrity support, of course, it also has a positive and significant influence on purchase intentions at shopee online stores and celebrity support has a positive and significant effect on customer trust in shopee online stores. consumers or customer trust has a positive and significant influence on purchase intentions at Shopee online stores.Social media marketing and customer trust have a very large influence on purchase intentions at Shopee online stores and have an important influence on purchase intentions mediated by customer trust in Shopee online stores in addition to endorsement parties also have an influence on celebrity purchases. on the Shopee online store.